Profil Jumlah Leukosit Berdasarkan Nilai Titer Widal pada Kasus Demam Tifoid Anak - Nurmansyah, Dian; Nisa, Shalehatun; Puspawati, Puspawati; Fayumi, Syihab; Mudzakkir, Musyirah; Sasmitha, Maya Herliana (JSN : Jurnal Sains Natural, 2025)
Typhoid fever, caused by Salmonella typhi infection, remains a public health issue in developing countries, including Indonesia, with the highest prevalence among children aged 5–14 years. This study aimed to analyze the leukocyte profile of pediatric typhoid fever patients at Graha Medika Clinic, Banjar Regency. An observational analytic design with a cross-sectional approach was used. The sample included 526 pediatric patients with Widal titers ?1/320 who underwent complete blood tests. Results revealed that 71.3% of patients had normal leukocyte counts, while 22.4% showed leukocytosis and 6.3% had leukopenia. Simple linear regression analysis indicated no significant relationship between Widal titers and leukocyte levels (R² = 0.002). These findings suggest that most pediatric typhoid fever cases present with normal leukocyte counts. Among abnormal cases, leukocytosis was more common, though leukopenia was also observed.